1. 390 : (4х + 3) = 26 2. 528 : (5х - 7) = 16
4х + 3 = 390 : 26 5х - 7 = 528 : 16
4х + 3 = 15 5х - 7 = 33
4х = 15 - 3 5х = 33 + 7
4х = 12 5х = 40
х = 12 : 4 х = 40 : 5
х = 3 х = 8
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
3. 594 : (8х - 55) = 18 4. 735 : (6х + 17) = 21
8х - 55 = 594 : 18 6х + 17 = 735 : 21
8х - 55 = 33 6х + 17 = 35
8х = 33 + 55 6х = 35 - 17
8х = 88 6х = 18
х = 88 : 8 х = 18 : 6
х = 11 х = 3
1. 390 : (4х + 3) = 26 2. 528 : (5х - 7) = 16
4х + 3 = 390 : 26 5х - 7 = 528 : 16
4х + 3 = 15 5х - 7 = 33
4х = 15 - 3 5х = 33 + 7
4х = 12 5х = 40
х = 12 : 4 х = 40 : 5
х = 3 х = 8
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
3. 594 : (8х - 55) = 18 4. 735 : (6х + 17) = 21
8х - 55 = 594 : 18 6х + 17 = 735 : 21
8х - 55 = 33 6х + 17 = 35
8х = 33 + 55 6х = 35 - 17
8х = 88 6х = 18
х = 88 : 8 х = 18 : 6
х = 11 х = 3
1. (√40 + 4)^2 - 16√10 = 56
2. (√87 - 7)^2 + 14*√3*√29 = 136
Пошаговое объяснение:
1. (√40 + 4)^2 - 16√10 = (2√10 + 4)²-16√10 = 40+16√10+16-16√10 = 56
2. (√87 - 7)^2 + 14*√3*√29 = 87-14√87+49+14√87=136